Acne treatment patterns, expectations, and satisfaction among adult females of different races/ethnicities - Rendon MI; Rodriguez DA; Kawata AK; Degboe AN; Wilcox TK; Burk CT; Daniels SR; Roberts WE (Dove Medical Press, 2015)
Marta I Rendon,1 David A Rodriguez,2 Ariane K Kawata,3 Arnold N Degboe,4 Teresa K Wilcox,3 Caroline T Burk,5 Selena R Daniels,4 Wendy E Roberts6 1Rendon Center for Dermatology and Aesthetic Medicine, Boca Raton, FL, USA; 2Dermatology Associates and Research, Coral Gables, FL, USA; 3Evidera, Bethesda, MD, USA; 4Allergan Inc., Irvine, CA, USA; 5Health Outcomes Consultant, Laguna Beach, CA, USA; 6Generational and Cosmetic Dermatology, Rancho Mirage, CA, USA Background: Limited data are available on acne treatment patterns, expectations, and satisfaction in the adult female subpopulation, particularly among different racial and ethnic groups. Objective: Describe acne treatment patterns and expectations in adult females of different racial/ethnic groups and analyze and explore their potential effects on medication compliance and treatment satisfaction. Methods: A cross-sectional, Web-based survey was administered to US females (25–45 years) with facial acne (≥25 visible lesions). Data collected included sociodemographics, self-reported clinical characteristics, acne treatment use, and treatment expectations and satisfaction. Results: Three hundred twelve subjects completed the survey (mean age, 35.3±5.9 years), comprising black (30.8%), Hispanic (17.6%), Asian/other (17.3%), and white (34.3%). More than half of the subjects in each racial group recently used an acne treatment or procedure (black, 63.5%; Hispanic, 54.5%; Asian/other, 66.7%; white, 66.4%). Treatment use was predominantly over-the-counter (OTC) (47.4%) versus prescription medications (16.6%). OTC use was highest in white subjects (black, 42.7%; Hispanic, 34.5%; Asian/other, 44.4%; white, 59.8%; P<0.05). The most frequently used OTC treatments in all racial/ethnic groups were salicylic acid (SA) (34.3%) and benzoyl peroxide (BP) (32.1%). Overall, compliance with acne medications was highest in white versus black (57.0±32.4 vs 42.7±33.5 days, P>0.05), Hispanic (57.0±32.4 vs 43.2±32.9 days, P>0.05), and Asian/other (57.0±32.4 vs 46.9±37.2 days, P>0.05) subjects. Most subjects expected OTC (73.7%) and prescription (74.7%) treatments to work quickly. Fewer than half of the subjects were satisfied with OTC treatment (BP, 47.0%; SA, 43.0%), often due to skin dryness (BP, 26.3%; SA, 44.3%) and flakiness (BP, 12.3%; SA, 31.1%). No statistically significant differences were observed among racial/ethnic groups in their level of satisfaction with OTC or prescription acne treatments. Conclusion: Racial/ethnic differences were observed in acne treatment patterns in adult females, while treatment expectations were similar. Results indicate that treatment patterns and expectations may impact treatment satisfaction and medication compliance. Keywords: acne, ethnicity, patient satisfaction, race, women